Modelling the Effect of Flexural Vibration on Sound Absorption of A Micro-perforated Panel Using Wave Propagation Method - Putra, Azma; Sajidin, Muhammad; Salleh, Norliana (Trans Tech Publications, 2014)
Micro-perforated panel (MPP) is well known as the alternative green sound absorbing material replacing the synthetic porous absorber. Several works have been established which model the sound absorption performance of the MPP with various arrangements. However, most existing models are for MPP with rigid condition and rarely discuss the effect of vibration due to the impinging sound. In this paper, a simple approach using wave propagation technique is proposed to take into account the effect of flexural wave in the MPP on its sound absorption. The model begins with an MPP coupled with a solid panel separated by an air gap. The impedance of the back solid panel can then be adjusted to a very large value to simulate a rigid wall.